Social Change in Iran : An Eyewitness Account of Dissent, Defiance, and New Movements for Rights - Yaghmaian, Behzad (Albany : SUNY Press, 2012)
Social Change in Iran is an inquiry into the recent changes in Iran, blending scholarly analysis, eyewitness accounts, and the author's personal experiences. It tells the stories of everyday people, be it young men and women challenging the cultural and social mandates of the Islamic Republic, or workers toiling at multiple jobs to overcome harsh economic realities. This passionate homage to the people of Iran as told by a native is a glimpse into the human feelings and aspirations of a people subjected to varying forms of violence at home and widespread misunderstanding abroad. At the same time Yaghmaian provides an informed analysis of the widening political divide within the state, and the emergence of a movement for reform, both of which have shaken the seemingly indisputable foundations of the Islamic Republic.
Front Matter -- Contents -- Acknowledgments -- Preface -- Iran: An Eyewitness Account and Study of Social Change -- Emerging Social Movements, Victories, and Setbacks in the Battle for Rights -- State and the Socialization of Violence: A Narrative of Everyday Life -- Children of the Islamic Republic -- Part I -- Children of the Islamic Republic -- Part II -- Children of the Islamic Republic -- Part III -- A Movement for a Free Press -- the Vanguard of the Battle for Rights and Civil Society -- State, Economy, and Civil Society -- Part I -- State, Economy, and Civil Society -- Part II -- Oil, International Division of Labor, and the Structural Crisis of the Iranian Economy: A Political Economy Analysis -- The Great Debate: A Republic or Velayat-E Faghih? -- Conclusions -- Postscript -- Notes -- Selected Bibliography -- Index
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Apr 2024).
JSTOR
Keywords: Civil society -- Iran; Social change -- Iran; Student movements -- Iran; Politics and Law : Democratization; Société civile -- Iran; Mouvements étudiants -- Iran; POLITICAL SCIENCE / Political Economy